(3CQHYhf MOjkKG ef GdEHOGd GdYhGdjs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s; (3GHf Whdhf , TeS GdOjf,J (B953 (3g` s
(3ChdgG (B:s
(3GeG HYO abO SCdfj HYV CTjGNj Cf CNQL CQHYjf MOjKkG ef GdEHOGd s
(3BNQgG (B:s
(3Yf CHf hgH ahbY HMeO Gddg hYahg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3JNQjLs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B54s
Keywords: (3GdMOjK h GdeUWdMs